PENGARUH PENERAPAN MODEL PEMBELAJARAN ARCS (ATENTTION, RELEVANCE, CONFIDENCE, SATISFACTION) TERHADAP HASIL BELAJAR MATEMATIKA - I Wayan Sumandya (Emasains : Jurnal Edukasi Matematika dan Sains, 2016)
The aim ofresearch was to determine (1) Whether or not the application of learning models ARCS influence on learning outcomes math class XI student of SMK Wira Harapanof the academic year 2016/2017, (2) To determine the students' response to the application of ARCS model of learning in mathematics.This research was conducted on a class XI student of SMK Wira Hope in the academic year 2016/2017. This study included quasi-experimental as well as with Matched Group Design. The population in this study are all class XI student of SMK Wira Harapan as many as 560 people and involved a sample of 60 people taken by simple random sampling technique. Student learning outcomes through mathematics achievement test. This study were analyzed by t-test, but previously tested the prerequisites are: normality test of data distribution and homogeneity of variance test.The results of learning achievement data analysis with significance level of 5% was obtained = 2,188, whereas = 2,045. Thus, greater than, means that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. This, showing no effects of the application of learning model ARCS on learning outcomes math class XI student of SMK Wira Harapan half of the school year 2016/2017. From the analysis of students' response to the application of ARCS learning model in the study of mathematics belongs in the positive.